1993 spring field report, Jim Fuller - Fuller, James L.et al (1993)
An annotated list of birds sighted by Jim Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed